PERAN PETUGAS KESEHATAN DENGAN TINGKAT PARTISIPASI POSYANDU LANSIA DI DESA ESANDOM SATU KECAMATAN TOMBATU TIMUR KABUPATEN MINAHASA TENGGARA - Silvia Dewi Mayasari Riu; Kristine Dareda (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2022)
This increase in the elderly population makes the government need to formulate policies and programs aimed at elderly population groups so that they can play a role in building public health. One of the government policies is that health services are provided at health centers, such as providing good and quality services, giving priority to elderly people and providing safe and easily accessible facilities, providing support or guidance to the elderly and their families on an ongoing basis. The purpose of this study was to determine the relationship between the role of health workers and the participation level of Posyandu for the elderly in Esandom one, Tombatu Timur District, Southeast Minahsa Regency. The study used a cross sectional analytic descriptive research method. The sample of respondents was 88 people using purposive sampling. Data collection using questionnaires and observation sheets. Analyzed with the chi square statistical test. The results of the study were 68 respondents (77.3%) with the highest age, 73 respondents (83.0%) had the highest education. Chi square test results obtained p value <? 0.05. The conclusion in this study is that there is a relationship between the role of health workers and the participation level of the Posyandu for the elderly in Esandom one, Tombatu Timur District, Southeast Minahsa Regency. Suggestions are expected that the Puskesmas can use this research as one of the bases in health promotion for the elderly.. Suggestions are expected that the Puskesmas can use this research as one of the bases in health promotion for the elderly.